Entrapped arterial sheath during transfemoral angiography - Javad Salimi; Alireza Majd; Sara Hosseini; Siavash Shariatzadeh; Mohamad Behzadi (Elsevier, 2021)
Arterial sheath entrapment is a potential complication during Trans Femoral Angiography. Here we are presenting a nine-month-old boy, a candidate for surgical repair of Tetralogy of Fallot, with complicated sheath entrapment. As the problem was not resolved initially by pharmacological approaches, later a transverse incision on the artery was made at the mid-length of the sheath. Subsequently, the device was splitted into two halves and both were successfully removed through the incision. This method facilitated the sheath withdrawal and diminished the trauma applied to the artery during surgery.